Research progress on zero-time exercise interventions in patients with chronic diseases: a narrative review - Ban, Guilan; Li, Chaxiang; Jin, Yue (Frontiers in Public Health, 2025)
Traditional exercise programs are often challenging for patients with chronic diseases due to time constraints, physical limitations, and other barriers. Zero-time exercise (ZETx) is an innovative approach that requires no additional time, equipment, or financial investment, making it particularly suitable for these patients. This narrative review aims to explore the conceptual framework, theoretical foundations, and health benefits of ZETx, as well as its acceptability and adherence among chronic disease patients. We conducted a comprehensive search in electronic databases (PubMed, Embase, Web of Science, Cochrane Library) using relevant search terms related to ZETx. Studies published in English and focusing on ZETx interventions were included. The search spanned from the inception of the databases to July 2025. ZETx interventions have demonstrated significant health benefits, including improvements in cardiorespiratory function, musculoskeletal health, cognitive function, and metabolic parameters. Additionally, ZETx has been found to be highly acceptable and feasible among chronic disease patients, with adherence rates exceeding those of traditional exercise programs. Future research should focus on standardizing exercise prescriptions, leveraging technological innovations such as wearable devices and virtual reality, and developing multidisciplinary intervention models. This approach has the potential to transform current practice paradigms in chronic disease management by providing a novel pathway for improving cardiovascular health, metabolic capacity, and overall wellbeing.